2019
DOI: 10.1037/xhp0000603
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric discrimination of nonspeech tonal analogues of vowels.

Abstract: Directional asymmetries reveal a universal bias in vowel perception favoring extreme vocalic articulations, which lead to acoustic vowel signals with dynamic formant trajectories and well-defined spectral prominences due to the convergence of adjacent formants. The present experiments investigated whether this bias reflects speech-specific processes or general properties of spectral processing in the auditory system. Toward this end, we examined whether analogous asymmetries in perception arise with non-speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…Specifically, we examined the auditory FFR in response to a less-focal/English prototypic /u/ and a more-focal/French prototypic /u/ in English-speaking adults, arranged in oddball and reversed-oddball blocks. Recent research by Masapollo and his colleagues (Masapollo et al, 2017a,b, 2019) has shown evidence, at the behavioral level, that directional asymmetries are driven by a universal sensitivity to formant proximity that operates independently of language-specific prototype categorization (contra Kuhl, 1991). The present study extends this work by providing neurophysiological evidence that formant convergence influences the neural discrimination of vowels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we examined the auditory FFR in response to a less-focal/English prototypic /u/ and a more-focal/French prototypic /u/ in English-speaking adults, arranged in oddball and reversed-oddball blocks. Recent research by Masapollo and his colleagues (Masapollo et al, 2017a,b, 2019) has shown evidence, at the behavioral level, that directional asymmetries are driven by a universal sensitivity to formant proximity that operates independently of language-specific prototype categorization (contra Kuhl, 1991). The present study extends this work by providing neurophysiological evidence that formant convergence influences the neural discrimination of vowels.…”
Section: Discussionmentioning
confidence: 99%
“…Current models and theories of speech perception provide insight into the potential mechanisms and processes underlying these directional asymmetries (Lahiri & Reetz, 2002; Kuhl et al, 2008; Polka & Bohn, 2011). The Natural Referent Vowel (NRV) framework, which is a model of early phonetic development (Polka & Bohn, 2011), has been used to guide a number of recent studies on vowel perception asymmetries (e.g., Masapollo, Polka, Molnar, & Ménard, 2017a; Masapollo, Polka, & Ménard, 2017b; Masapollo, Zhao, Franklin & Morgan, 2019). In this model, directional asymmetries are argued to reflect a universal sensitivity to prominent spectral peaks formed by the convergence of adjacent formants.…”
Section: Introductionmentioning
confidence: 99%
“…See Supplemental Material S1 for further details regarding analyses of stimulus order effects (see, e.g., Masapollo et al, 2018). 5 The finding that the present oral-motor manipulations did not influence the perception of static visual speech may be indirectly related to other findings showing that the acoustic and visual information for speech perception includes dynamic (time-varying) information (such as formant transitions and oral-facial kinematic patterns) and static target information (e.g., Masapollo et al, 2018;Masapollo, Zhao, Franklin, & Morgan, 2019;Strange, 1989;Viswanathan, Magnuson, & Fowler, 2014). visual information in talking faces.…”
mentioning
confidence: 80%
“…Finally, although the preponderance of evidence suggests that asymmetries in vowel perception derive from cognitive encoding strategies involving attention and working memory rather than general auditory processes ( Polka and Bohn, 2011 ; Masapollo et al, 2017b , 2018b ), analogous effects have also been reported with non-speech tonal analogues of vowels that approximate some of the temporal characteristics of naturally-produced /u/ vowels executed with more versus less extreme lip gestures ( Masapollo et al, 2019 ). While such findings may be interpreted as evidence that asymmetries reflect (at least in part) general auditory processing biases, it is also possible that they reflect fundamentally different types of processes than those captured using speech stimuli (see also, Bishop et al, 2005 ; Timm et al, 2011 ).…”
Section: Discussionmentioning
confidence: 94%
“…As highlighted in Masapollo et al (2017b , 2018a) , NRV assumes that the effects of formant convergence on vowel perception reflect a phonetic bias that emerges when listeners are perceiving speech , rather than a low-level sensitivity to raw acoustic energy . Compatible with this view, perception experiments have demonstrated that asymmetries predicted by differences in formant proximity are observed whether vowels are heard or perceived visually in a lip-reading task ( Masapollo et al, 2017b , 2018a ; Masapollo and Guenther, 2019 ), confirming that the “focal vowel” bias derives from phonetic processing rather than low-level psychoacoustic processes ( Masapollo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 83%